The Correlation Between EFL Students' Reading Attitude and Their Reading Comprehension at Fourth Semester of English Department at University of Islam Malang - Dian Rahayu Safitri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT : Reading is important activity for all people especially for student to get the point of reading text to support them in pedagogic area or for communication purposes. And because of that students have to have good comprehension in reading. But, for English as a foreign language (EFL) learner sometimes reading becomes challenging because of some obstacless such as lack of vocabulary, background knowledge and reading attitude. Then, beside that is so limited study regarding to students L2 reading attitude in reading in EFL learner at college level. Moreover, the current study seeks to answer research problem, do the higher score students’ reading attitude, the higher score their comprehension in reading.            This current study uses quantitative research to measure the data. The current study involves the correlational variable between reading attitude as variable (X) and reading comprehension as variable (Y). The population of the study is 30 students of fourth semester of English Department of University of Islam Malang from Class A and B. The current study uses two variables there are Reading Attitude questionare and TOEFL reading test to assess students’ readign comprehension and both are measured with Pearson Product Momment coefficient correlation through SPSS version 2.0.            The finding of the currents study shows that there is no correlation between students’ reading attitude and their reading comprehension. It is proven by the r value -.176 and the score of significancy .353 and that is higher than 0.05. Keywords:Reading, reading attitude, reading comprehension